Electrochemically activated EA-ZnCo2O4-coated CoWO4 composite material and preparation method thereof
The EA-ZnCo2O4@CoWO4 composite material is processed through electrochemical activation technology to form a heterostructure that combines nanowires and nanosheets, which solves the problems of poor conductivity and low active position utilization of CoWO4 materials, and significantly improves the electrical power of supercapacitors Chemical properties, especially in charge storage and rate performance, show excellent results.
Patent Information
- Application Number
- CN202411463492.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
Cobalt tungsten oxide (CoWO4) materials face poor conductivity and low surfactant utilization in practical applications, which limits their electrochemical performance improvement in supercapacitors.
Electrochemical activation technology was used to treat EA-ZnCo2O4@CoWO4 composite material, and nanowire-shaped ZnCo2O4 precursor was synthesized by hydrothermal reaction and annealing. Then, cyclic voltammetry was used in the three-electrode system to form uniformly distributed nanowires ZnCo2O4@nanoflake CoWO4 heterostructure enhances the redox reaction site and conductivity of the material.
It significantly improves the specific capacitance and rate performance of the electrode material, and the material structure is more dispersed. The tip nanosheets are connected to form a curved sheet with a larger size and thinner thickness. It efficiently absorbs OH- in the solution, stores charge, and shows that Higher electrochemical properties.
Smart Images

Figure CN119296989A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitors, and in particular relates to an electrochemically activated EA-ZnCo2O4@CoWO4 composite material and a preparation method thereof. Background Art
[0002] With the consumption of fossil fuels, it is urgent to develop efficient and green energy storage and conversion technologies. Supercapacitors have attracted widespread attention due to their high power density, fast charge and discharge speed, long cycle life and environmental friendliness. Electrode materials are the key to developing high-performance supercapacitors. Cobalt tungsten oxide (CoWO4) has attracted much attention due to its diverse valence states, abundant reserves and environmental friendliness. However, CoWO4 materials still face challenges such as poor conductivity and low utilization of surface active sites in practical applications.
[0003] To solve these problems, core-shell structure design provides an effective strategy. The core-shell structure can not only improve the overall conductivity and charge transfer efficiency of the material, but also increase the number of active sites, thereby improving the electrochemical performance of the electrode material. However, the preparation of the core-shell structure is usually complicated, and the instability of the interface bonding may limit the further improvement of its performance. Electrochemical activation, as a surface treatment technology, provides a new idea for improving the electrochemical performance of the core-shell structure. By activating the material in an electrochemical environment, not only can the active sites on the surface of the material be increased and the rapid transfer of charge be promoted, but also a microstructure that is more conducive to charge storage can be formed through surface reconstruction. Summary of the invention
[0004] The present invention provides an electrochemically activated EA-ZnCo2O4@CoWO4 composite material and a preparation method thereof. The method not only utilizes the synergistic effect between the heterogeneous structures of ZnCo2O4 and CoWO4 to increase the redox reaction sites of the material, but also can adjust the microstructure of the material through electrochemical activation, enhance the charge transfer rate, and thus improve the electrochemical performance of the electrode material.
[0005] A method for preparing an electrochemically activated EA-ZnCo2O4@CoWO4 composite material comprises the following steps: synthesizing a nickel foam containing a nanowire-shaped ZnCo2O4 precursor by hydrothermal reaction and annealing treatment, loading CoWO4 nanosheets on the nickel foam containing the ZnCo2O4 precursor by secondary hydrothermal treatment to synthesize ZnCo2O4@CoWO4, and activating ZnCo2O4@CoWO4 by cyclic voltammetry in a three-electrode system to obtain the EA-ZnCo2O4@CoWO4 composite material.
[0006] A method for preparing an electrochemically activated EA-ZnCo2O4@CoWO4 composite material specifically comprises the following steps: (1) dissolving a zinc source, a cobalt source, ammonium fluoride and urea in deionized water in proportion, stirring with ultrasound to form a uniform solution, transferring the solution and nickel foam to a reactor for a first hydrothermal reaction, taking out the nickel foam after the reaction, washing and drying it, and then annealing it to obtain a nickel foam containing a ZnCo2O4 precursor; the ZnCo2O4 precursor is in the form of nanowires; (2) dissolving a cobalt source and a tungsten source in deionized water and stirring to form a uniform solution, then transferring the nickel foam containing a ZnCo2O4 precursor and the above solution to a hydrothermal reactor for a secondary hydrothermal reaction, and after the reaction, taking out the nickel foam and washing and drying it to obtain ZnCo2O4@CoWO4; the ZnCo2O4@CoWO4 is a nanowire@nanosheet heterostructure; (3) A three-electrode system was constructed with ZnCo2O4@CoWO4 as the working electrode, Pt as the counter electrode and Hg / HgO as the reference electrode. Cyclic voltammetry was used for electrochemical activation in KOH solution. After activation, the working electrode was rinsed several times with ethanol and deionized water and dried to obtain the EA-ZnCo2O4@CoWO4 composite material.
[0007] Furthermore, in step (1), the zinc source is zinc nitrate hexahydrate, and the cobalt source is cobalt nitrate hexahydrate; the molar ratio of the zinc source, the cobalt source, ammonium fluoride and urea is 1:2:2:5.
[0008] Furthermore, in step (1), the first hydrothermal reaction temperature is 140° C. and the hydrothermal time is 6 h.
[0009] Furthermore, in step (1), the annealing temperature is 350° C. and the annealing time is 2 h.
[0010] Furthermore, in step (2), the cobalt source is cobalt nitrate hexahydrate, and the tungsten source is sodium tungstate dihydrate; the molar ratio of the cobalt source to the tungsten source is 1:1.
[0011] Furthermore, in step (2), the second hydrothermal reaction temperature is 150° C. and the hydrothermal time is 6 h.
[0012] Furthermore, in step (3), the scan rate of the cyclic voltammetry is 50-100 mV / s, the activation potential window is 0-0.7 V, and the number of activation cycles is 1-100 cycles.
[0013] Furthermore, the molar concentration of the KOH solution in step (3) is 3M.
[0014] The EA-ZnCo2O4@CoWO4 composite material is prepared by the above preparation method.
[0015] The beneficial effects of the present invention are: The present invention synthesized the EA-ZnCo2O4@CoWO4 composite material. The uniformly distributed nanowire ZnCo2O4@nano-sheet CoWO4 heterostructure increases the redox reaction sites and conductivity of the material. After electrochemical activation, the structure of the material is more dispersed, and the nanosheets at the tip are connected to form a larger and thinner nano-curved sheet, which can efficiently adsorb OH in the solution. - And store charge, showing high specific capacitance and good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 CV curves of ZnCo2O4@CoWO4, ZnCo2O4@CoWO4-1, and ZnCo2O4@CoWO4-2 activated for 100 cycles under different conditions (a) 0~0.7 V, 50 mV / s; (b) 0~0.7 V, 100 mV / s; (c) 0~0.8 V, 50 mV / s.
[0017] Figure 2 These are (a) XRD patterns of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, and EA-ZnCo2O4@CoWO4; (b) XRD patterns of EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1, and EA-ZnCo2O4@CoWO4-2.
[0018] Figure 3 SEM images of (a, b) CoWO4; (c, d) ZnCo2O4; (e, f) ZnCo2O4@CoWO4 at different magnifications.
[0019] Figure 4 SEM images of (a, b) EA-ZnCo2O4@CoWO4; (c, d) EA-ZnCo2O4@CoWO4-1; (e, f) EA-ZnCo2O4@CoWO4-2 at different magnifications.
[0020] Figure 5 (a) CV curves of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4 at a scan rate of 5 mV / s; (b) CV curves of EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 at a scan rate of 5 mV / s.
[0021] Figure 6CV curves of (a) CoWO4; (b) ZnCo2O4; (c) ZnCo2O4@CoWO4; (d) EA-ZnCo2O4@CoWO4; (e) EA-ZnCo2O4@CoWO4-1; (f) EA-ZnCo2O4@CoWO4-2 at different scanning rates.
[0022] Figure 7 (a) GCD curves of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 at current density of 1 A / g; (b) specific capacitance of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 at current density of 1, 2, 5, 8 and 10 A / g.
[0023] Figure 8 (a) The Nyquist curves and equivalent circuit fitting diagrams of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2; (b) is a local enlarged view of the Nyquist curve. DETAILED DESCRIPTION
[0024] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0025] Example 1 EA-ZnCo2O4@CoWO4 composite material (1) Nickel foam treatment The nickel foam was immersed in acetone and 3 M hydrochloric acid solution for 20 min, then washed with deionized water and anhydrous ethanol solution for 3 times, and finally dried at 60 °C for 6 h.
[0026] (2) Synthesis of ZnCo2O4 precursor 0.297 g Zn(NO3)2·6H2O, 0.582 g Co(NO3)2·6H2O, 0.0745 g NH4F and 0.301 g urea were dissolved in 35 mL deionized water and ultrasonically stirred for 0.5 h to form a uniform solution. The treated nickel foam and the above solution were transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and reacted at 140°C for 6 h. The nickel foam was taken out, washed with deionized water and ethanol several times, and dried at 60°C for 12 h. The dried nickel foam was placed in a crucible and annealed at 350°C for 2 h to obtain a nickel foam containing a ZnCo2O4 precursor.
[0027] (3) Synthesis of ZnCo2O4@CoWO4 0.291 g Co(NO3)2·6H2O and 0.330 g Na2WO4·2H2O were dissolved in 30 mL deionized water and stirred at 1000 rpm for 5 min to obtain a uniform solution. The nickel foam containing the ZnCo2O4 precursor and the above solution were transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and reacted at 150°C for 6 h. The nickel foam was taken out, washed with deionized water and ethanol several times, and dried at 60°C for 12 h to obtain ZnCo2O4@CoWO4.
[0028] (4) Synthesis of EA-ZnCo2O4@CoWO4 In 3 M KOH solution, a three-electrode system was constructed using ZnCo2O4@CoWO4 as the working electrode, platinum sheet as the counter electrode and Hg / HgO as the reference electrode. CV electrochemical activation was performed for 1 to 100 cycles at a potential window of 0 to 0.7 V and a scan rate of 50 mV / s. The activated electrode was rinsed several times with ethanol and deionized water and dried at 60°C for 12 h to obtain EA-ZnCo2O4@CoWO4.
[0029] Example 2 EA-ZnCo2O4@CoWO4-1 composite material The steps for synthesizing ZnCo2O4@CoWO4 were the same as those in Example 1. In a 3 M KOH solution, a three-electrode system was constructed using ZnCo2O4@CoWO4 as a working electrode, a platinum sheet as a counter electrode, and Hg / HgO as a reference electrode. CV electrochemical activation was performed for 1 to 100 cycles at a potential window of 0 to 0.7 V and a scan rate of 100 mV / s. The activated electrode was rinsed several times with ethanol and deionized water, and dried at 60°C for 12 h to obtain EA-ZnCo2O4@CoWO4-1.
[0030] Example 3 EA-ZnCo2O4@CoWO4-2 composite material The steps for synthesizing ZnCo2O4@CoWO4 were the same as those in Example 1. In a 3 M KOH solution, a three-electrode system was constructed using ZnCo2O4@CoWO4 as a working electrode, a platinum sheet as a counter electrode, and Hg / HgO as a reference electrode. CV electrochemical activation was performed for 1 to 100 cycles at a potential window of 0 to 0.8 V and a scan rate of 50 mV / s. The activated electrode was rinsed several times with ethanol and deionized water, and dried at 60°C for 12 h to obtain EA-ZnCo2O4@CoWO4-2.
[0031] Comparative Example 1 Preparation of CoWO4 (1) Nickel foam treatment The nickel foam was immersed in acetone and 3 M hydrochloric acid solution for 20 min, then washed with deionized water and anhydrous ethanol solution for 3 times, and finally dried at 60 °C for 6 h.
[0032] (2) Synthesis of CoWO4 Dissolve 0.291 g Co(NO3)2·6H2O and 0.330 g Na2WO4·2H2O in 30 mL deionized water and stir for 5 min. Transfer a piece of treated nickel foam and solution to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and react at 150°C for 6 h. Take out the nickel foam, wash it with deionized water and ethanol several times, and dry it at 60°C for 12 h to obtain CoWO4.
[0033] Figure 1 (ac) are the CV curves of ZnCo2O4@CoWO4 activated for 100 cycles under different conditions. The results show that the response current of the electrode increases rapidly and tends to be stable in the early cycles, and the specific capacitance increases during the CV cycle.
[0034] Figure 2(a) XRD patterns of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4. The strong diffraction peaks at 2θ of 44.5°, 51.8° and 76.4° belong to the nickel foam matrix. The characteristic peaks at 18.9°, 30.6°, 36.4° and 54.0° correspond to the monoclinic CoWO4 (PDF#72-0479). Due to the lower crystallinity or mass loading of CoWO4, its diffraction peak intensity is weak. For ZnCo2O4, the diffraction peaks at 18.9°, 31.2°, 36.8°, 38.4°, 59.2° and 65.1° match the (111), (220), (311), (222), (511) and (400) crystal planes of card 23-1390. ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4-1 all have all the characteristic peaks of CoWO4 and ZnCo2O4, indicating that the phase of the electrode has not changed after CV activation. Figure 2 As shown in (b), the diffraction peaks of EA-ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4-1 did not change significantly, while the diffraction peak of CoOOH (PDH#26-0480) appeared in EA-ZnCo2O4@CoWO4-2, indicating that the electrochemical activation by changing the scan rate will not cause phase change, while the electrochemical activation by changing the voltage window will produce oxygen absorption reaction and some active substances will undergo irreversible phase change.
[0035] Figure 3 The SEM images of CoWO4, ZnCo2O4, and ZnCo2O4@CoWO4 at different magnifications are shown below. Figure 3 As shown in (a, b), CoWO4 is a two-dimensional nanosheet with a rough surface. The nanosheets grow evenly on the nickel foam and are densely distributed. Figure 3 In (c), the ZnCo2O4 morphology is mainly nanowire structure. From the high magnification SEM ( Figure 3 (d) It can be seen that the ZnCo2O4 nanowires are composed of many nanowires with smaller diameters, with a diameter of 90-110 nm, and a large number of pores are formed between the staggered nanowire arrays. Figure 3 As shown in (e, f), CoWO4 nanosheets grow vertically on the ZnCo2O4 nanowire skeleton to form a ZnCo2O4@CoWO4 core-shell heterostructure. The core-shell heterostructure combines the structures of the two components well, which may be beneficial for providing additional electrochemical reaction active sites for the electrode material and improving its electrochemical performance. Figure 4(a, b) and (c, d) show that the morphology of EA-ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4-1 is similar to that of ZnCo2O4@CoWO4. However, the structures of EA-ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4-1 are more dispersed, and the nanosheets at their tips are connected to form a curved sheet-like structure with larger size and thinner thickness. Figure 4 As shown in (e, f), the tips of the heterostructures of EA-ZnCo2O4@CoWO4-2 approached each other and aggregated.
[0036] Figure 5 (a) CV curves of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4 at 5 mV / s. After normalization, EA-ZnCo2O4@CoWO4 has the largest CV integral area, indicating that the electrochemically activated core-shell heterostructure provides more active sites for it, promotes the redox reaction, and significantly increases the specific capacitance. Figure 5 As shown in (b), the electrochemical performance of EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 has been improved, but it is still lower than that of EA-ZnCo2O4@CoWO4. This is because the activation of the active material is not completely activated when the voltage window is not changed and the scan rate is increased; while the electrochemical activation with a voltage window of 0~0.8 V at a constant scan rate will produce an oxygen absorption side reaction, causing phase change of some active materials and aggregation of the morphology. Figure 6 As shown in (a)-(f), CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 electrodes all show obvious redox peaks, which are consistent with the typical battery-type Faraday reaction characteristics. With the increase of the scan rate, the shape of the CV curve of the electrode does not change significantly, but peaks I and II shift to the positive and negative potential directions, respectively, which may be due to the hysteresis of electron transfer kinetics caused by the electrode ohmic voltage drop and polarization effect.
[0037] like Figure 7As shown in (a), the specific capacitances of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 at 1 A / g are 1203.8 F / g, 1507.6 F / g, 2606.7 F / g, 3266.5 F / g, 2934.4 F / g and 2836.0 F / g, respectively, indicating that the EA-ZnCo2O4@CoWO4 electrode has the largest specific capacitance. EA-ZnCo2O4@CoWO4 exhibits the largest specific capacitance at current densities of 1, 2, 5, 8, and 10 A / g, and can maintain 70.1% of its initial capacity even at 10 A / g ( Figure 7 (b)), indicating that the electrochemically activated composite material of the present invention has good rate performance.
[0038] The charge transfer reaction kinetics of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 were analyzed by EIS. Figure 8 As shown in (a, b), the fitting circuit consists of an equivalent series resistance (R s ), constant phase element (CPE), Warburg impedance (Z w )、Charge transfer resistance (R ct ) and Faraday pseudocapacitance (C F ) s is the intersection value of the high frequency region and the real axis (Z'), which is composed of electrolyte resistance, interface contact resistance and material intrinsic resistance. EA-ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4-1 have the smallest R s (Table 1), indicating that the electrochemically activated heterostructure can improve the diffusion pathway of ions, thereby promoting the transfer of charges. The semicircle diameter in the mid-frequency region represents R ct , which reflects the charge transfer process between the electrolyte and the material surface. The slope of the low-frequency curve represents Z w , the larger the slope, the smaller the diffusion resistance of the material and the faster the electrolyte ion diffusion rate. Specifically, the R ct They are 5.22 Ω, 0.23 Ω, 1.34 Ω, 0.69 Ω, 0.94 Ω and 1.07 Ω respectively. ctThe slopes of the two materials are between CoWO4 and ZnCo2O4, indicating that the charge transfer kinetics and ion diffusion rate are improved, but still slightly inferior to ZnCo2O4. This phenomenon may be due to the complexity of the interface interaction between the two heterostructure materials, which may affect the charge transfer efficiency to some extent.
[0039] Table 1 Fitting data of equivalent circuits of CoWO4, ZnCo2O4, ZnCo2O4@CoWO4 and EA-ZnCo2O4@CoWO4, EA-ZnCo2O4@CoWO4-1 and EA-ZnCo2O4@CoWO4-2 electrodes In summary, the present invention adopts a combination of hydrothermal and electrochemical activation processes, using ZnCo2O4 as a precursor to synthesize EA-ZnCo2O4@CoWO4 composite materials. At a current density of 1 A / g, the specific capacitance of EA-ZnCo2O4@CoWO4 is as high as 3266.5F / g, and it can still maintain a capacity retention rate of 70.1% at 10 A / g. EA-ZnCo2O4@CoWO4 exhibits excellent electrochemical performance, which is attributed to: (1) The heterostructure of nanowires and nanosheets provides more active sites for electrochemical reactions, improving the charge storage capacity of the electrode. (2) The heterostructure provides more permeation paths for the diffusion of electrolytes, improving the charge and discharge efficiency of the electrode. (3) Electrochemical activation optimizes the surface structure of the electrode, making the heterostructure more dispersed, and the nanosheets at the tips are connected to form a curved sheet with a larger size and thinner thickness, which is conducive to the diffusion and adsorption of electrolyte ions.
[0040] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing an electrochemically activated EA-ZnCo2O4@CoWO4 composite material, characterized in that: Nickel foam containing nanowire-like ZnCo2O4 precursor was synthesized by hydrothermal reaction and annealing treatment. CoWO4 nanosheets were loaded on the nickel foam containing ZnCo2O4 precursor by secondary hydrothermal treatment to synthesize ZnCo2O4@CoWO4. Cyclic voltammetry was used to activate ZnCo2O4@CoWO4 in a three-electrode system to obtain EA-ZnCo2O4@CoWO4 composite material.
2. The preparation method according to claim 1, characterized in that: The specific steps include: (1) dissolving a zinc source, a cobalt source, ammonium fluoride and urea in deionized water in proportion, stirring with ultrasound to form a uniform solution, transferring the solution and nickel foam to a reactor for a first hydrothermal reaction, taking out the nickel foam after the reaction, washing and drying it, and then annealing it to obtain a nickel foam containing a ZnCo2O4 precursor; the ZnCo2O4 precursor is in the form of nanowires; (2) dissolving a cobalt source and a tungsten source in deionized water and stirring to form a uniform solution, then transferring the nickel foam containing a ZnCo2O4 precursor and the above solution to a hydrothermal reactor for a secondary hydrothermal reaction, and after the reaction, taking out the nickel foam and washing and drying it to obtain ZnCo2O4@CoWO4; the ZnCo2O4@CoWO4 is a nanowire@nanosheet heterostructure; (3) A three-electrode system was constructed with ZnCo2O4@CoWO4 as the working electrode, Pt as the counter electrode and Hg / HgO as the reference electrode. Cyclic voltammetry was used for electrochemical activation in KOH solution. After activation, the working electrode was rinsed several times with ethanol and deionized water and dried to obtain the EA-ZnCo2O4@CoWO4 composite material.
3. The preparation method according to claim 2, characterized in that: In step (1), the zinc source is zinc nitrate hexahydrate, and the cobalt source is cobalt nitrate hexahydrate; the molar ratio of the zinc source, the cobalt source, ammonium fluoride and urea is 1:2:2:
5.
4. The preparation method according to claim 2, characterized in that: The first hydrothermal reaction temperature in step (1) is 140° C. and the hydrothermal time is 6 h.
5. The preparation method according to claim 2, characterized in that: In step (1), the annealing temperature is 350° C. and the annealing time is 2 h.
6. The preparation method according to claim 2, characterized in that: In step (2), the cobalt source is cobalt nitrate hexahydrate, and the tungsten source is sodium tungstate dihydrate; the molar ratio of the cobalt source to the tungsten source is 1:
1.
7. The preparation method according to claim 2, characterized in that: The second hydrothermal reaction temperature in step (2) is 150° C. and the hydrothermal time is 6 h.
8. The preparation method according to claim 2, characterized in that: In step (3), the scan rate of the cyclic voltammetry is 50-100 mV / s, the activation potential window is 0-0.7 V, and the number of activation cycles is 1-100 cycles.
9. The preparation method according to claim 2, characterized in that: The molar concentration of the KOH solution in step (3) is 3M.
10. The EA-ZnCo2O4@CoWO4 composite material prepared by the preparation method according to any one of claims 1 to 9.